SISTEM KONTROL LACI PERALATAN MENGGUNAKAN PERINTAH SUARA - Widyaningrum Firdausi; Berlina Zalika; Eko Sulistyo; Muhammad Iqbal Nugraha (Politeknik Manufaktur Negeri Bangka Belitung, 2022)
Along with technological developments, device systems can now be controlled using voice commands via smartphones. The use of voice commands as a control system is one of the most widely used operating systems today. The equipment drawer is a place for storing items whose work system is pulled and applied by the user, and security only by using a manual key. To make it easier to control the opening and closing of the drawer in this study, voice commands will be added to control it. The research method is to change the voice command sent via a smartphone with a command code created with the mit app inventor software, the results of the voice to text conversion will manage the microcontroller and the output will activate the L298N relay and driver to open and close via the solenoid lock as an electric switch and motor. dc as drive. This is done by giving commands via a smartphone with input from several different users and observing the control response on the solenoid lock working or not and measuring the maximum distance that the user can test. From the test results as many as 4 different user voices on the drawer open and close control can work well. The percentage of success is 90%, failure 10% is caused by a less clear articulation of the voice commands given. Testing the maximum distance that can be controlled is approximately 10 meters.